Community-Based Instruction (CBI) as a Component of a Successful Transition Plan for Students with Intellectual Disabilities - Dubberly, Russell (Journal of the American Academy of Special Education Professionals, 2012)
This research study used a student-focused questionnaire to gain understanding about high school students with intellectual disabilities who participate in community-based instruction (CBI) as a component of their transition planning. The participating students have intellectual disabilities, range in age from 16 years old to 22 years old, and attend a public school for students with special needs. The survey used descriptive statistics to quantify students’ responses within five sub-domains ("constructs") which were categorized as program satisfaction, learning, self-esteem, independent functioning, and social skills.